Policy Reversals, Lobby Groups and Economic Distortions - Rafaelita M. Aldaba (Philippine Institute for Development Studies (PIDS), 2005)
This paper aims to review the impact of the various tariff legislations passed from 1998 to 2003 on the structure of protection in the Philippines. The paper finds that while the overall level of effective protection has declined, it has remained uneven as some selected sectors have continued to receive relatively high effective rates of protection. As such, the economic distortions that characterize our tariff structure have continued to prevail and have led to the inefficient use of resources. The tariff structure continues to favor the manufacture of highly protected import substitutes at the expense of exportables. Oftentimes, the favored sectors are intermediate goods like sugar, petrochemicals, float glass, and steel which are inputs to a lot of products. Since the tariffs on the inputs are higher than the outputs, the cost of production has remained high affecting the competitiveness of the user sectors. The large disparities in tariff protection has provided incentives for lobbying. Thus, sustaining the trade reforms and encouraging competition to promote efficiency and consumer welfare has been very difficult.
Keywords: 330; tariff structure; effective protection rate; trade policies; Protektionismus; Zollpolitik; Zoll; Außenwirtschaftspolitik; Philippinen